Key lifestyles and interim health outcomes for effective interventions in general populations: A network analysis of a large international observational study - Li, Jiaying; Fong, Daniel Yee Tak; Lok, Kris Yuet Wan; Wong, Janet Yuen Ha; Ho, Mandy Man; Choi, Edmond Pui Hang; Pandian, Vinciya; Davidson, Patricia M; Duan, Wenjie; Marie, Tarrant; Lee, Jung Jae; Lin, Chia-Chin; et al. (International Society of Global Health, 2023)
Background The interconnected nature of lifestyles and interim health outcomes implies the presence of the central lifestyle, central interim health outcome and bridge lifestyle, which are yet to be determined. Modifying these factors holds immense potential for substantial positive changes across all aspects of health and lifestyles. We aimed to identify these factors from a pool of 18 lifestyle factors and 13 interim health outcomes while investigating potential gender and occupation differences.